Video classes production and math learning in high school groups at IFSul campus Pelotas (Research, Society and Development, 2020)
Many authors have dedicated their researches to topics related to the use of technologies in education. Traditional classes with only a blackboard and some chalks are not attractive anymore and also do not stimulate the curiosity about the topics approached. Nowadays, students are used to immediate answers, obtained through online researches and they do not have the necessary patience to be concentrated in a traditional class.  This study reports an experience which proposed, based on the concept of investigative activity, for high school students, the planning, the execution and editing of video classes containing topics approached in the classroom.  The main objective of this study was the learning of content, but the motivations were also as it follows: the challenge of creativity to elaborate a script which incentives the viewer to watch the video; the research and use of software for editing the videos; the understanding of content to demonstrate confidence in the explanation of the class. Two of the videos, resulting of the experience and which are reported, surpassed the expectations of the teacher. With the results obtained, it is concluded that the students who devoted themselves to the tasks obtained quite significant learning, which can be observed throughout the classes which were continued after the study was carried out.